2019
DOI: 10.1016/j.jpainsymman.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatigue, Pain, and Depression in Patients With Advanced Kidney Disease and Cancer—Symptom Burden and Clusters

Abstract: Context. Although symptom clusters have been studied in the context of cancer, few data exist in chronic and end-stage kidney disease (CKD/ESKD) patients. Objectives. The objectives of this study were to 1) characterize and compare symptom cluster phenotypes in patients with advanced CKD, ESKD, and cancer and 2) explore predictors of symptom clusters. Methods. We conducted secondary data analysis of three prospective studies in which pain, depression, and fatigue were assessed in patients with Stage 4e5 CKD, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 48 publications
(60 reference statements)
4
67
0
1
Order By: Relevance
“…A recent study of 606 gastrointestinal cancer patients reported that 9.6% experienced the fatigue-pain-depression symptom cluster [27]. Higher figures have been reported in studies of patients with lung cancer (19%), which is often advanced at diagnosis, patients with advanced cancer (20%) and patients following a palliative pathway (27%) [11,28,29]. In terms of possible explanations for the lower observed prevalence of the symptom cluster in the current study population, this may be because the majority of survivors had localized disease at diagnosis and many had survived 10 years or more.…”
Section: Prevalence Of the Symptom Clustermentioning
confidence: 94%
See 1 more Smart Citation
“…A recent study of 606 gastrointestinal cancer patients reported that 9.6% experienced the fatigue-pain-depression symptom cluster [27]. Higher figures have been reported in studies of patients with lung cancer (19%), which is often advanced at diagnosis, patients with advanced cancer (20%) and patients following a palliative pathway (27%) [11,28,29]. In terms of possible explanations for the lower observed prevalence of the symptom cluster in the current study population, this may be because the majority of survivors had localized disease at diagnosis and many had survived 10 years or more.…”
Section: Prevalence Of the Symptom Clustermentioning
confidence: 94%
“…Cancer-related pain, fatigue and depression are recognized to co-exist in a ‘symptom cluster’ among cancer patients and survivors [ 9 11 ]. Moreover, there is some evidence that the immune/inflammation pathway provides a biological basis for the co-existence of these symptoms in a cluster [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with both end-stage kidney disease and earlier stages of CKD report high symptom-burden that has a negative influence on health-related quality of life (HRQOL) [10][11][12][13][14]. Notably, frailty is independently associated with worse HRQOL in CKD populations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is one of the most common symptoms, reported by 30%‐60% of patients with end‐stage kidney disease (ESKD) 1‐3 . In fact, the prevalence of pain in this population is similar to that in patients with advanced cancer 3 . Unfortunately, pain is frequently underdiagnosed and undertreated in ESKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, pain is frequently underdiagnosed and undertreated in ESKD patients. Fewer than 50% of hemodialysis (HD) patients with pain report using analgesics, and 75% have ineffective pain management 2,4,5 . Untreated pain negatively impacts patient's health‐related quality of life (HRQOL), dialysis adherence, healthcare utilization, and mortality 6‐8 .…”
Section: Introductionmentioning
confidence: 99%